Conclusion Of Non-exclusive Discount Agreements According To 130a Para. 8 Sgb V On Medicinal Products (open-house Procedure) [Tender documents : T487403780] (MENA Report, 2023)
Contract notice: conclusion of non-exclusive discount agreements according to 130a para. 8 sgb v on medicinal products (open-house procedure) This ohv is not subject to public procurement law and has already been eu 2023/s 079-237358 published in the supplement to the official gazette of the eu (first publication). the customer has expanded the procurement requirements for this procedure and hereby announces this in accordance with its announcement under section ii.2.4) of the initial announcement and section a.I.4.1 of the conditions of participation (follow-up announcement). aok bw intends to enter into non-exclusive discount agreements with all suitable pharmaceutical companies in accordance with section 130a para. 8 sgb v on medicines with the active ingredients named in appendix 3 to the conditions of participation. the contract period begins for the active substances/combinations of active substances according to para. ii.2.4) of the first publication no earlier than 07/01/2023 and is a maximum of 24 months. the contract period begins for the active substances/combinations of active substances according to para. ii.2.4) of this follow-up notice no earlier than 08/01/2023 and is a maximum of 23 months.The procurement requirements of ohv 2023 include all medicinal products with the active ingredients specified in annex 3 to the conditions of participation (so-called list of active ingredients and deadlines). the aok baden-wuerttemberg (aok) has the procurement requirements of the already announced abl. eu 2023/s 079-237358 announced open-house procedure extended in such a way that also for the medicinal products with the following combination of active ingredients within the framework of this open-house procedure agreements according to 130a para. 8 sgbv are to be closed: beclometasone dipropionate + formoterol hemifumarate-1-water (serial no. 10 of annex 3 to the conditions of participation, as of 31.05.2023). annex 3 to the conditions of participation was supplemented accordingly and is subordinate to the interested companies free registration - together with the other procedural documents - on the award platform (see item i.3) of this announcement). the aok reserves the right to expand the procurement requirements of this open-house procedure in the course of the further procedure with further active ingredients. the conditions of participation (section a.I.4.1) contain more detailed information on a possible expansion of the procurement requirements. combination of active ingredients will be closed with effect from august 1st, 2023 at the earliest. all discount contracts concluded as part of this open-house procedure end on 06/30/2025. for the earliest possible start of discount contracts with the above combination of active ingredients on august 1st, 2023, interested companies must submit a complete offer according to the participation documents exclusively in electronic form via the communication area of the award platform by june Major organization : AOK BADEN-WRTTEMBERG Address : Presselstrae 19 Country :Germany Email : ohv@bw.aok.de Url : www.aok.de/bw Tender notice number : 334083-2023 Notice type : T489360570.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).